Quadratic root law (one of the store models) to change the rent of the houses - Khula Ismaeel (College of Education for Pure Sciences, 2009)
ABSTRACT Most of houses' owners try to increase the houses' rental prices from time to time. However this increase will be taken place, but the real income of the owners declines, that is because of many different costs that the owner will carry out. This research includes the following question "How long should the houses' owners rise the houses' rental prices?" The Economic Optimal Quantity size (EOQ) formula used to derive two equations, first for houses have constant value, second for houses have increasing market value during the time. Moreover, these two equations determine the increase rate of houses' rental price and the optimal period of changing the rental price for both situations.